Ekspresi Matrix Metalloproteinase-9 (MMP-9), HER-/neu, dan Metastasis Kelenjar Getah Bening pada Karsinoma Payudara Duktal Invasif - Threeyana Ariyati Kadi; Faroek Hoesin (Majalah Patologi Indonesia, 2015)
Background Lymph nodes metastases is the important major prognostic factor in predicting breast cancer mortality. HER-2/neu overexpression will make worse prognosis. MMP-9 is related to tumor invasion and metastases by their capacity to degrade basement membrane. Assessing HER-2/neu and MMP-9 expression before metastates occur is expected to be useful for prognostic and therapeutic assessment that can prevent patient deaths. Methods A retrospective study with cross sectional analytic approach was done. Assessment was performed on paraffin blocks of breast cancer patients who were diagnosed in Dr. Soetomo Hospitals during January 2011-December 2012 and met the criteria. MMP-9 expression was analyzed imunohistochemically. The relation between MMP-9, HER-2/neu, and lymph node metastases was investigated by Chi Square (ï£2) tests. Results There were 26 out of 40 breast cancer cases with lymph nodes metastases, 22 of 26 cases with MMP-9 overexpression (2+ and 3+), and only 10 cases with HER-2/neu overexpression (3+). MMP-9 overexpression was 12 of 17 cases with positive HER-2/neu. There is statistically significant correlation between MMP-9 expression and lymph nodes metastases (p=0.011); whereas there is no statistical significant correlation between expression of HER-2/neu and MMP-9 (p=0.583) and between HER-2/neu expression and lymph nodes metastases (p=0.435). Conclusion MMP-9 is signifantly correlated with lymph nodes metastases. No significant relationship was found between HER-2/neu, MMP-9 and lymph nodes metastasis. Key words : breast cancer, HER-2/neu, lymph nodes metastases, MMP-9.